Leukotoxin production by Fusobacterium necrophorum biotypes - Tan, Z.; Chengappa, M. M.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Fusobacterium necrophorum biotypes A and B were grown anaerobically to detect their leukotoxin production. Both biotypes exerted the highest leukotoxic effect on bovine leukocytes in the late logarithmic and early stationary growth places. Biotype A produced more leukotoxin than biotype B throughout all phases of bacterial growth. Results are consistent with the findings that biotype A is more virulent than biotype B.
Keywords: Beef; Leukotoxin; F. necrophorum; Biotype; Growth phase; Liver abscesses